Acute Exacerbation and Respiratory InfectionS in COPD (AERIS): protocol for a prospective, observational cohort study. Issue 3 (7th March 2014) - Bourne, Simon; Cohet, Catherine; Kim, Viktoriya; Barton, Anna; Tuck, Andy; Aris, Emmanuel; Mesia-Vela, Sonia; Devaster, Jeanne-Marie; Ballou, W Ripley; Clarke, Stuart; Wilkinson, Tom
Abstract : Introduction: The aetiology of acute exacerbations of chronic obstructive pulmonary disease (COPD) remains incompletely understood and strategies for treatment and prevention have not altered significantly for many years. Improved understanding of the role of respiratory pathogens in acute exacerbations of COPD (AECOPD) is required and the use of molecular microbiological techniques may lead to insights into host–pathogen interactions and the development of more targeted therapeutic approaches. Methods and analyses: Acute Exacerbation and Respiratory InfectionS in COPD (AERIS) is a longitudinal epidemiological study to assess how changes in the COPD airway microbiome contribute to the incidence and severity of AECOPD. Patients with COPD aged 40–85 are followed monthly for 2 years, and reviewed within 72 h of onset of symptoms of AECOPD. Exacerbations are detected using daily electronic diary cards. Blood, sputum, nasopharyngeal and urine samples are collected at prespecified timepoints. Molecular diagnostic and typing techniques are used to describe the dynamics of airway infection during AECOPD and stable disease, and associations with clinical outcome. This study aims to refine the case definition of AECOPD to reflect the possible microbiological aetiology. AERIS will assess the impact of AECOPD on health-related quality of life and healthcare resource utilisation, and the possible interactions between nutritional status, infection and immune responses. Ethics and dissemination: AERIS is conducted in accordance with the Declaration of Helsinki and Good Clinical Practice, and has been approved by the institutional ethics and review board. All participants must provide written informed consent. The results obtained will be disseminated at international medical conferences and in peer-reviewed publications. Discussion: Few other studies have addressed the complexity of the microbiological and systemic components of COPD or employed real-time electronic tracking of symptoms to identify AECOPD and potential aetiological triggers. Results: Results of AERIS will increase our understanding of the contribution of pathogens to AECOPD, potentially leading to new targeted therapeutic and preventative interventions. Trial registration number: ClinicalTrials.gov NCT01360398 .